Clonal evolution of multidrug resistant hepatitis B virus during entecavir rescue therapy. (13th May 2015) - Chon, Young E.; Jin, Bora; Ahn, Sang H.; Kim, Seungtaek; Kim, Nam D.; Park, Jeon H.; Nam, Chung M.; Kim, Kyun‐Hwan; Hong, Sun P.; Choi, Sung H.; Kim, Do Y.; Park, Jun Y.; et al.
Abstract Background & Aims Analysing the mutation pattern of multidrug resistance (MDR) is important in the treatment of chronic hepatitis B (CHB). In this study, the evolutionary pattern of MDR mutations was investigated in patients receiving entecavir (ETV) rescue therapy. Methods Eight CHB patients with lamivudine (LAM)‐ and adefovir (ADV)‐resistant mutations showing suboptimal response to ETV and to subsequent ETV‐plus‐ADV therapy were enrolled. The clonal evolution of the mutation pattern was investigated through direct sequencing, multiplex restriction fragment mass polymorphism (RFMP), and clonal analysis and the utility of these methods was compared. Results Among 160 clones at baseline, wild‐type hepatitis B virus (HBV) was present in 62 (38.8%), LAM‐resistant mutations in 92 (57.6%) and ADV‐resistant mutations in 55 (34.4%). LAM‐resistant mutations increased to 70.6% at the end of ETV therapy and increased to 74.4% at the 12th month of ETV‐plus‐ADV therapy. During the same time periods, ETV‐resistant mutations were present in 46.3% and 38.8%, and ADV‐resistant mutations were present in 3.1% and 9.4% respectively. When 256 nucleotides from 32 samples were examined for mutations, clonal analysis detected 93 mutations (36.3%), direct sequencing detected 36 mutations (14.1%) and RFMP detected 73 mutations (28.5%). The sensitivity (73.1%, 95% CI; 64.1–82.1%) and specificity (96.9%, 95% CI; 94.4–99.4%) of RFMP were high, showing a concordance rate of 88.3% with the results from clonal analysis. All mutations exceeding 40% of the total clones detected by clonal analysis were also detected by RFMP. Conclusions The clonal evolution of the mutation pattern in MDR HBV showed the selection of LAM‐resistant (±ETV‐resistant) HBV during ETV rescue therapy, which may be the primary reason for patients' suboptimal response. Multiplex RFMP is a useful method for detecting MDR mutations in clinical practice.